DNA Profiling: How Long is the Golden Snitch’s Flesh Memory? - Chandla, Danny; Parish, Siobhan (Journal of Interdisciplinary Science Topics, 2017)
Will the Flesh Memory of the Golden Snitch really last seven years? The Golden Snitch is a ball used in the game of Quidditch that remembers the first person to have contact with its surface. Analysis of forensic techniques, in particular DNA profiling and the effects of temperature are used to model whether the Snitch would recognise Harry Potter seven years later. If stored at room temperature (21oC), this would not be possible. The model is then extended to calculate the average temperature of storage required for this to be possible, 10.08oC.